Ceramic coating as well as preparation method and application thereof
By preparing ceramic coatings on 95% alumina ceramics, using materials such as chromium oxide, manganese oxide or zinc oxide to reduce the secondary electron emission coefficient and adjust the surface resistivity, the surface flashover phenomenon of alumina ceramics in vacuum electronic devices is solved. The problem of low voltage resistance is achieved by increasing the vacuum along the plane flashover voltage and reducing power loss.
Patent Information
- Application Number
- CN202411521291.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
95% alumina ceramics are used to restrict the development of vacuum electronic devices due to the flashover along the plane and low voltage resistance in vacuum electronic devices, which affects the reliability of the device. Especially under high power, high frequency and miniaturization conditions, it restricts the development of vacuum electronic devices.
Use chromium oxide with low secondary electron emission coefficient and manganese oxide or zinc oxide with low surface resistivity, combined with silicon oxide and calcium oxide that can react with base ceramics to prepare ceramic coatings, spray on the surface of insulating support materials, and reduce secondary electrons. The emission coefficient and the surface resistivity are adjusted to increase the vacuum along the plane flashover voltage.
The vacuum flickering voltage of the insulating support material is significantly improved, power loss is reduced, the device is operated efficiently, and it provides good adhesion. It is suitable for microfocus X-ray tubes and high-power broadband cyclobar tubes.
Smart Images

Figure CN119390433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of alumina ceramic surface coatings, and more specifically, to a ceramic coating and a preparation method and application thereof. Background Art
[0002] Microwave vacuum electronic devices are the heart of national defense military equipment systems and are widely used in various equipment systems such as high-power microwave weapons, electronic reconnaissance and early warning, satellite navigation, electronic interference and countermeasures. In vacuum devices, insulating structural ceramics play the role of high-voltage insulation, vacuum sealing, power transmission, and support and fixation. Among various vacuum electronic devices today, 95% alumina ceramics are widely used for their excellent electromechanical properties. Due to the surface flashover phenomenon, the pressure resistance of 95% alumina ceramics is much lower than its body breakdown strength and the pressure resistance strength of vacuum gaps of the same size. The entire system often breaks down under the action of a lower electric field. As vacuum devices develop towards high power, high frequency and miniaturization, the operating voltage of vacuum electronic devices has doubled, making the surface flashover phenomenon of alumina ceramics an important factor affecting their reliability and restricting the development of vacuum electronic devices. Therefore, the development of ceramic coatings with high vacuum surface flashover voltage is of great significance to the development of vacuum electronic devices.
[0003] The surface condition of the insulating support material is a direct factor affecting its surface withstand voltage performance. Coating a coating material with a low secondary electron emission coefficient and low resistivity on the surface of the insulating support material can inhibit the generation and accumulation of surface charge and effectively improve its vacuum surface flashover voltage. Among them, the secondary electron emission coefficient is a direct factor affecting the vacuum surface flashover voltage. Reducing the secondary electron emission coefficient can reduce the probability of surface flashover of the ceramic and increase the vacuum surface flashover voltage. Secondly, too high surface resistivity is not conducive to the discharge of surface charge, increases the local field strength, and makes surface flashover more likely to occur. Therefore, it is necessary to reduce the surface resistivity to a certain extent and improve the surface charge discharge capacity. However, as an insulating support material, the surface resistivity of 95% alumina ceramic cannot be too low. If the surface resistivity of the insulating support material is too low due to the coating material, it will cause the leakage current of the device to be too large, resulting in excessive power loss of the power supply and abnormal heating of the device. Especially when used for microfocus X-ray tubes, if the surface resistivity of the ray tube continues to decrease by an order of magnitude from E14Ω, the power loss may exceed 1 / 3 of the power supply power, seriously affecting the use of the device. Summary of the invention
[0004] The first object of the present invention is to provide a ceramic coating. The present invention combines chromium oxide with a low secondary electron emission coefficient with manganese oxide or zinc oxide with a low surface resistivity, and silicon oxide and calcium oxide that can react with the base ceramic to prepare the ceramic coating. After spraying on the surface of the insulating support material, the secondary electron emission coefficient can be significantly reduced and the surface resistivity can be adjusted, thereby increasing the vacuum surface flashover voltage of the insulating support material and making the power loss relatively low. At the same time, the coating has good adhesion and is suitable for use in microfocus X-ray tubes and high-power broadband cyclotron traveling wave tubes as a functional coating.
[0005] The second object of the present invention is to provide a method for preparing the ceramic coating as described above.
[0006] A third object of the present invention is to provide a ceramic coating.
[0007] The fourth object of the present invention is to provide an application of the ceramic coating as described above in the preparation of a microfocus X-ray tube and a high-power broadband cyclotron traveling wave tube.
[0008] In order to achieve the first objective, the present invention discloses a ceramic coating, which comprises the following raw materials in parts by weight:
[0009]
[0010] Due to the requirements of microfocus X-ray tubes for vacuum surface flashover voltage and power loss, the present invention combines chromium oxide with a low secondary electron emission coefficient with manganese oxide or zinc oxide with a low surface resistivity to prepare a ceramic coating for use in microfocus X-ray tubes. By adjusting the composition of the ceramic coating formula, the obtained ceramic coating can not only improve the vacuum surface flashover voltage of alumina ceramics, but also will not significantly affect the power loss of alumina ceramics.
[0011] Furthermore, the ceramic coating comprises the following raw materials in parts by weight:
[0012]
[0013] or
[0014] The ceramic coating comprises the following raw materials by weight:
[0015]
[0016] To achieve the second objective, the present invention discloses a method for preparing the ceramic coating as described above, comprising the following steps:
[0017] Weigh a certain amount of manganese oxide or zinc oxide, as well as chromium oxide, silicon oxide and calcium oxide, and perform ball milling and sieving to obtain a mixed powder;
[0018] A solvent is added to the mixed powder, and a paste-like ceramic coating is obtained by secondary ball milling, wherein the solvent is selected from one of pinene alcohol, niter-cotton solution, and butyl acetate.
[0019] Furthermore, in one ball milling, the ratio of the sum of the masses of the raw material powders to the mass of the grinding balls is 1:1.5, and the one ball milling time is 18-24 hours.
[0020] Furthermore, in the secondary ball milling, the mass ratio of the mixed powder, the solvent and the grinding ball is 1:1-3:1, and the secondary ball milling time is 18-24 hours. When pine alcohol, niter cotton solution or butyl acetate is selected as the solvent of the system, the obtained ceramic coating can have better fluidity.
[0021] Furthermore, the grinding balls are made of alumina balls with a particle size of 8-12 mm.
[0022] To achieve the third purpose mentioned above, the present invention discloses a ceramic coating prepared using the ceramic coating as described above, specifically, the ceramic coating is evenly sprayed on the surface of a microfocus X-ray tube or a high-power broadband cyclotron traveling wave tube, and the ceramic coating is obtained after sintering.
[0023] Furthermore, the sintering temperature is 1250-1500° C., and the sintering time is 2-5 hours.
[0024] Furthermore, the microfocus X-ray tube or high-power broadband gyrotron traveling wave tube is made of 95% alumina ceramic.
[0025] Furthermore, the dry film thickness of the ceramic coating is 30-50 μm.
[0026] The ceramic coating increases the vacuum surface flashover voltage of the micro-focus X-ray tube and simultaneously makes the power loss of the micro-focus X-ray tube no more than 5%.
[0027] In order to achieve the fourth objective, the present invention discloses an application of the ceramic coating as described above in the preparation of a microfocus X-ray tube and a high-power broadband cyclotron traveling wave tube.
[0028] The beneficial effects of the present invention are as follows:
[0029] The present invention combines chromium oxide with a low secondary electron emission coefficient with manganese oxide or zinc oxide with a low surface resistivity, and silicon oxide and calcium oxide that can react with base ceramics to prepare a ceramic coating. After being sprayed on the surface of an insulating support material, its secondary electron emission coefficient can be significantly reduced and its surface resistivity can be adjusted, thereby increasing the vacuum surface flashover voltage of the insulating support material and making the power loss relatively low. At the same time, it has good adhesion. As a functional coating, it is suitable for applications in microfocus X-ray tubes and high-power broadband cyclotron traveling wave tubes, and is particularly suitable for microfocus X-ray tubes that have requirements for vacuum surface flashover voltage and power loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0031] Figure 1 The microscopic morphology of the ceramic coating prepared in Example 1 of the present invention is shown, wherein Figure 1 (a) is UV, and (b) is BSE.
[0032] Figure 2 The secondary electron emission coefficient test spectrum of the ceramic coating prepared in Examples 1-5 of the present invention is shown, wherein: Figure 2 Among them, (a) is Example 1, (b) is Example 2, (c) is Example 4, (d) is Example 5, and (e) is Example 3.
[0033] Figure 3 The secondary electron emission coefficient test spectrum of the 95% alumina ceramic used in the present invention is shown. DETAILED DESCRIPTION
[0034] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0035] Unless otherwise specified, the raw materials used in the present invention can be obtained commercially. Any range recorded in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0036] Example 1
[0037] Chromium oxide, manganese oxide, silicon oxide and calcium oxide were mixed in a mass ratio of 65:30:3:2, and mixed in a roller ball mill for 24 hours using aluminum oxide balls at a material-ball ratio of 1:1.5;
[0038] The mixed powder is passed through a 150-mesh sieve to obtain a mixed powder;
[0039] Add terpineol to the mixed powder, and place the mixed powder, terpineol and alumina balls in a roller ball mill at a mass ratio of 1:2:1 for 24 hours to obtain a paste-like ceramic coating.
[0040] The prepared ceramic coating was evenly sprayed on a 95% alumina ceramic substrate, placed in a high-temperature furnace, and sintered at 1300° C. for 3 hours to obtain a ceramic coating.
[0041] The microstructure of the ceramic coating was tested by SEM. Figure 1 As shown in Figure 2, it can be seen that the microstructure of the ceramic coating after heat treatment is uniform and dense.
[0042] The prepared ceramic coating was subjected to the following performance tests, and the test results are shown in Table 1:
[0043] 1) Use a high resistance meter to measure the surface resistivity of the sample.
[0044] 2) The three-gun method is used to measure the secondary electron emission coefficient. For the test device and principle, please refer to the following document [Measurement of total electron emission yield of insulators based on self-terminating charge neutralization]. The three-gun method can eliminate the influence of accumulated charge on the surface of ceramic materials and ensure the accuracy of the measurement results. The measuring gun is used to emit primary electrons. The electron beam is incident vertically on the sample. The energy range of the incident primary electron is 0-3500eV, the incident current is 0.1μA, and the pulse width is 5μs. Two neutralization guns are used to neutralize the surface charge of the ceramic. The three guns work together to obtain the secondary electron emission coefficient test spectrum. Figure 2 , taking 95% alumina ceramic before spraying as the control, its secondary electron emission coefficient test spectrum Figure 3 .
[0045] 3) The vacuum surface flashover voltage test uses a DC high voltage vacuum test system. The test sample thickness is 5mm. When the vacuum degree of the test chamber reaches 1×10 -4 The test starts at 1.500 Pa. During the test, a negative polarity DC voltage with a linear increase rate of 500 V / s is applied to the sample until surface flashover occurs. Then the voltage is gradually reduced until the surface flashover phenomenon disappears completely. This voltage value is applied 3 times. If it is completely stable, the voltage at this time is recorded as the vacuum surface flashover voltage of the sample.
[0046] Example 2
[0047] Chromium oxide, zinc oxide, silicon oxide and calcium oxide were mixed in a mass ratio of 65:30:3:2, and mixed in a roller ball mill for 24 hours using aluminum oxide balls at a material-to-ball ratio of 1:1.5;
[0048] The mixed powder is passed through a 150-mesh sieve to obtain a mixed powder;
[0049] A niter-cotton solution was added to the mixed powder, and the mixed powder, the niter-cotton solution and the alumina balls were placed in a rolling bottle ball mill at a mass ratio of 1:1:1 and rolled for 24 hours to obtain a paste-like ceramic coating.
[0050] The prepared ceramic coating was evenly sprayed on a 95% alumina ceramic substrate, placed in a high-temperature furnace, and sintered at 1300° C. for 3 hours to obtain a ceramic coating.
[0051] The performance of the prepared ceramic coating was tested according to the test method of Example 1. The test results are shown in Table 1.
[0052] Example 3
[0053] Chromium oxide, manganese oxide, zinc oxide, silicon oxide and calcium oxide were mixed in a mass ratio of 60:20:15:3:2, and mixed in a roller ball mill for 24 hours using aluminum oxide balls at a material-to-ball ratio of 1:1.5;
[0054] Pass the mixed powder through a 150-mesh sieve;
[0055] Add terpineol to the mixed powder, and place the mixed powder, terpineol and alumina balls in a roller ball mill at a mass ratio of 1:2:1 for 24 hours to obtain a paste-like ceramic coating.
[0056] The prepared ceramic coating was evenly sprayed on a 95% alumina ceramic substrate, placed in a high-temperature furnace, and heat-treated at 1300° C. for 3 hours to obtain a ceramic coating.
[0057] The performance of the prepared ceramic coating was tested according to the test method of Example 1. The test results are shown in Table 1.
[0058] Example 4
[0059] Chromium oxide, zinc oxide, silicon oxide and calcium oxide were mixed in a mass ratio of 65:30:3:2, and mixed in a roller ball mill for 24 hours using aluminum oxide balls at a material-to-ball ratio of 1:1.5;
[0060] The mixed powder is passed through a 150-mesh sieve to obtain a mixed powder;
[0061] Add terpineol to the mixed powder, and roll-mill the mixed powder, terpineol and alumina balls in a roller ball mill at a mass ratio of 1:1:1 for 24 hours to obtain a paste-like ceramic coating.
[0062] The prepared ceramic coating was uniformly sprayed on a 95% alumina ceramic substrate, placed in a high-temperature furnace, and heat-treated at 1400° C. for 2 hours to obtain a ceramic coating.
[0063] The performance of the prepared ceramic coating was tested according to the test method of Example 1. The test results are shown in Table 1.
[0064] Example 5
[0065] Chromium oxide, zinc oxide, silicon oxide and calcium oxide were mixed in a mass ratio of 65:30:3:2, and mixed in a roller ball mill for 24 hours using aluminum oxide balls at a material-to-ball ratio of 1:1.5;
[0066] The mixed powder is passed through a 150-mesh sieve to obtain a mixed powder;
[0067] Butyl acetate was added to the mixed powder, and the mixed powder, butyl acetate and alumina balls were placed in a roller ball mill at a mass ratio of 1:1:1 for 24 hours to obtain a paste-like ceramic coating.
[0068] The prepared ceramic coating was evenly sprayed on a 95% alumina ceramic substrate, placed in a high-temperature furnace, and heat-treated at 1500° C. for 2 hours to obtain a ceramic coating.
[0069] Table 1
[0070]
[0071] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A ceramic coating, characterized in that: The ceramic coating comprises the following raw materials by weight:
2. The ceramic coating according to claim 1, characterized in that: The ceramic coating comprises the following raw materials by weight: or The ceramic coating comprises the following raw materials by weight:
3. The method for preparing a ceramic coating according to claim 1 or 2, characterized in that: The steps include: Weigh a certain amount of manganese oxide or zinc oxide, as well as chromium oxide, silicon oxide and calcium oxide, and perform ball milling and sieving to obtain a mixed powder; A solvent is added to the mixed powder, and a paste-like ceramic coating is obtained by secondary ball milling, wherein the solvent is selected from one of pinene alcohol, niter-cotton solution, and butyl acetate.
4. The preparation method according to claim 3, characterized in that: In one ball milling, the ratio of the sum of the masses of the raw material powders to the mass of the grinding balls is 1:1.5, and the ball milling time is 18-24 hours.
5. The preparation method according to claim 3, characterized in that: In the secondary ball milling, the mass ratio of the mixed powder, the solvent and the grinding balls is 1:1-3:1, and the secondary ball milling time is 18-24h.
6. The preparation method according to claim 4 or 5, characterized in that: The grinding balls are made of alumina balls with a particle size of 8-12 mm.
7. A ceramic coating, characterized in that: The ceramic coating according to claim 1 or 2 is uniformly sprayed on the surface of a microfocus X-ray tube or a high-power broadband cyclotron traveling wave tube, and then sintered to obtain a ceramic coating.
8. The ceramic coating according to claim 7, characterized in that The sintering temperature is 1250-1500°C and the sintering time is 2-5h.
9. The ceramic coating according to claim 7, characterized in that The material of the micro-focus X-ray tube or the high-power broadband cyclotron traveling wave tube is 95% alumina ceramic.
10. Use of the ceramic coating according to claim 1 or 2 in the preparation of microfocus X-ray tubes and high-power broadband cyclotron traveling wave tubes.
Citation Information
Patent Citations
Ceramic surface coating method
CN104496549A
High-radiation wear-resistant energy-saving coating and preparation method thereof
CN104557088A
Electric-insulation ceramic coating material and preparation method thereof
CN104557139A
Ceramic X-ray pipe inner surface coating composition and sintering method thereof
CN108395280A
X-ray tube
CN115274383A